Miscellaneous Marine Fishes Caught under PFZ and Non-PFZ Realm off Ratnagiri Coast, Maharashtra State, India - Tingote RS; Mane UH (International Journal of Aquaculture and Fishery Sciences - Peertechz Publications, 2017)
Potential Fishing Zones connote where Chlorophyll Concentration and Sea Surface Temperature together constitute better environment for the healthy growth of fish and food abundance. Fishing was done in both within and outside PFZ zones after validating PFZ advisory in time and firsthand information is also collected from the fish catch in different gears by following generated PFZ advisory and feedback in the standard format developed by INCOIS. Within PFZ means potential and good number of fish catch is obtained as compared to outside PFZ means fishing is done away 2-3km without using PFZ advisory. Identical boats were selected at the same time from the same landing centers going one in within and other for outside PFZ fishing boats separately carried fishing operations in accordance with the PFZ area provided by the satellite. The availability of food is an important factor that controls their occurrence, abundance and migrations in the sea. Sea Surface Temperature (SST) is the most easily observed environmental parameter and is quite often correlated with the availability of fish, especially pelagic fish. A better understanding of the behavior and dynamics of fish populations including their response to environmental and anthropogenic pressures is essential for effective management of marine fisheries. In spite of the vast scope and potentials for development of marine fishery along Ratnagiri coast, significant and tangible progress needs to be achieved so far through INCOIS-DOD which is leading to benefit the fishermen community in obtaining high fi sh catch with less efforts and time and fuel saving from PFZ, still much is needed to work based on a few drawbacks and gaps as seen (a) lack of sufficient understanding PFZ, (b) failure to recognize the PFZ during fishing, (c) lack of modernizing or upgrading the mechanized boats, and (d) little infrastructure and equipment in fishing. The INCOIS-DOD Mission activities should be thoroughly and critically is followed both by fishermen and their societies on the Ratnagiri coast region for which the expansion of this Mission and extension of research activities. The successful validation on PFZ advisory from the three fi sh landing centers were conducted during the study tenure.